Digital Cash: Implementation Issues And Impact On The Banking And Monetary System In Malaysia - R. Ramasamy, Sockalingam (2007)
This thesis explores the development and implementation issues of e-money in Malaysia, particularly the adoption, diffusion and usage of MEPS cash and Touch 'n Go cards. This thesis also examines the macro-economic implications particularly, the impact of e-money on the monetary aggregates such as currency denominations, currency circulations, money supply, the balance sheet and seignorage revenue of the central bank.